In-hospital Falls in Older Patients: The Risk Factors and The Role of Hyponatraemia - Harianto, Harry; Anpalahan, Mahesan (Current Aging Science, 2017)
Background: Hyponatraemia has been associated with increased falls risk. However, this has not been adequately investigated in the context of In-Hospital Falls (IHFs). Objectives: To determine the potential risk factors for IHFs, particularly the role of hyponatraemia. Methods: Patients aged >65 years with an incident IHF during admissions under a General Internal Medicine (GIM) Unit over six months were studied. For each case, two age and sex matched controls were randomly selected from patients who were admitted under the GIM unit during the same time as the cases. The relevant data were obtained by review of medical records. Results: The prevalence of IHF was 7.2%. Hyponatraemia had a significant univariate association with IHF (P=0.005). This association remained significant even after controlling the covariates (adjusted odds ratio (OR) 1.890, 95% confidence interval (CI) 1.391-3.497, P=0.021). The frequency of IHF did not vary with the severity of hyponatraemia (P=0.267). The other variables that had an independent association with IHFs were admission falls (OR 1.570, CI 1.340-5.833, P=0.030), use of psychotropic medications (OR=4.440, CI 2.051-13.240, P <0.001) and diuretics (OR=0.827, CI 0.767-0.901, P=0.010), and cardiovascular diagnosis (OR=0.916, CI 0.893-0.942, P=0.039). Conclusion: Hyponatraemia has an independent association with increased risk of IHFs. Other potential risk factors for IHFs include admission falls and psychotropic medication use. Diuretic use and cardiovascular diagnosis have a significant inverse association with IHFs.
Keywords: in-hospital falls